Imagining a Better World: Black Futurity in Contemporary Afrofuturism and Speculative Fiction - Dyer-Johnson, Omara Samirah (2022)
Originally coined in the 1990s, the term Afrofuturism has become a prominent part of popular culture and has helped to address the absence of Black people and cultures from speculations about the future. Many texts have been labelled as examples of Afrofuturism by critics, scholars and fans, though identifying the key aspects of the genre is challenging. This thesis argues that integral to the genre is the question: what is a ‘better’ world? I contend that an integral part of Afrofuturism is the author’s desire to imagine a ‘better’ world and that each author presents an alternative consideration of what a ‘better’ world is or should be. This project focuses on contemporary expressions of Afrofuturism as existing scholarship has been primarily concerned with defining the genre, historicising it, and constructing an Afrofuturist canon. However, contemporary texts conceive of ‘better’ worlds in ways that differ from the established Afrofuturist canon. To demonstrate the various perspectives concerning Black futurity, each chapter considers a different perspective concerning Black futurity from utopian isolationist futures to futures that approach climate change and environmentalism. Contemporary Afrofuturism has further developed the ideas in canonical texts and these varying speculations both indicate the changing terrain of the genre and exemplify the versatility of contemporary Afrofuturism and Black speculative fiction. Afrofuturism is difficult to define because of these varying approaches, yet this breadth of perspectives is integral to the genre and its ability to challenge the absence of Black futurity in popular culture. Despite the difficulty of defining the term, Afrofuturism is and remains a genre that can significantly change the way we think about who belongs in the future.